The False Dichotomy of Sex and Religion in America. (8th February 2022) - Burke, Kelsy
Abstract: Religion and sexuality are polysemic categories. While conservative religion often fights against progressive sexual politics in contemporary America, this "usual story" is fractured and destabilized by people navigating the relationship between religion and sexuality as complex social creatures, not pundits or caricatures. Drawing from interdisciplinary scholarship, I examine salient issues of sexual politics—including abortion and reproductive rights, LGBT rights, and pornography—to show how religious actors have been on both sides of these debates. Because of this polysemic complexity, scholars of religion must not only tend to the dynamic interaction between religion and other categories, we must also recognize and study the diversity within the categories themselves.